Developing a prototype e-commerce application with credit card validation and secure transaction - M. A., Ameedeen (2005)
Shopping today has been a problem for many people since more people nowadays have less time to shop. Therefore many are actually switching to e-commerce applications. Anyhow,the problem with e-commerce application is that many of them are not secure.This application is designed to enhance the e-commerce applications with additional security items.The security enhancement made was integrating an encryption module that secures the data that are stored in the databases. The application also includes an online credit card validation module that validates credit cards against the Luhn Algorithm and predefined credit card prefixes.The application will accept three types of credit cards which are Mastercard,Visa and American Express.The application is developed on the NET platform using ASP.NET and Visual Basic NET scripting.Therefore,the application could run on all kinds of platform.The application requires a Microsoft Server based operating system and Microsoft SQL Server in order for it to run.The application has been tested and runs successfully both on a server and on a workstation with server settings.In short,this system is the solution to the problems of current e-commerce technology.